1975
DOI: 10.1063/1.430227
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pressure dependence of the nuclear quadrupole interaction of 23Na in NaClO3

Abstract: The data were taken with a spectrometer described by Robinson 6 and modified by Dutcher and Scott. 7 The frequency measurements were conventional. The frequen-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Since the experiments have indicated that the pressure derivative of frequency is independent of temperature, it can be concluded that A γ = 0; only the static contribution β s γ is significant to the change resulting from the application of a small uniaxial stress. Evidence of this type of behaviour has been reported in other cubic crystals such as NaClO 3 [26] and NaBrO 3 [27]. The parameter β s γ is related to the stress tensor σ and the strain tensor ε, through the expression β d γ =∑ kl Q k S kl (∂σ l /∂P) γ with S kl = (∂ε k /∂σ l ) T .…”
Section: Line Shapesmentioning
confidence: 76%
“…Since the experiments have indicated that the pressure derivative of frequency is independent of temperature, it can be concluded that A γ = 0; only the static contribution β s γ is significant to the change resulting from the application of a small uniaxial stress. Evidence of this type of behaviour has been reported in other cubic crystals such as NaClO 3 [26] and NaBrO 3 [27]. The parameter β s γ is related to the stress tensor σ and the strain tensor ε, through the expression β d γ =∑ kl Q k S kl (∂σ l /∂P) γ with S kl = (∂ε k /∂σ l ) T .…”
Section: Line Shapesmentioning
confidence: 76%